The management puzzle solved! : hiring, developing, managing, leading - Hammes, Richard G. (Productivity Press, 2026)
Most often managers come up through the ranks of employees and are chosen because of their success, drive, abilities, education, other accomplishments, and personal factors. However, collectively their accomplishments as employees do not necessarily prepare them for managing and leading. Completing tasks is different from energizing and motivating others to perform. Often the best "doers" are not the best managers. In managing and leading, it often is the mid-level or average performer that is more effective. They may not achieve at the highest level as an employee, but they have qualities that fit with the characteristics of successful managers and leaders. What is needed regardless of prior experience is training and guidance to be a successful manager and leader. What they need is a tool kit to assist them in transitioning to management and, more broadly, to grow in the role over many years. The contents of this book are based on 30 years of client-proven consulting work with companies from start-up to Fortune 100. The information, methods, forms, and other ideas have been honed and modified to provide a universally implementable series of programs and processes that will assist managers and leaders at all levels of organizations to more effectively lead and manage. A key value of The Management Puzzle Solved! is that useful management information is communicated in a concise, informative, non-time intensive format. Each section can be read and digested readily and serve as an ongoing reference for managers as specific needs or concerns arise or just to broaden knowledge.This book is a mini-management course in a readable and compact format. It provides managers with information to interview candidates more effectively, deal with the day-to-day management of employees, provide leadership for the organization, manage employee performance, facilitate meetings effectively, enhance communication, promote team functioning, and implement change more smoothly. Rather than the latest fad, this field-tested set of management tools provides ideas and techniques that have been implemented in hundreds of companies with thousands of managers and employees to help you manage and lead effectively.